Evaluation of inflammatory cytokines as prognostic markers in experimental acute pancreatitis in rats - Paran,Haim (2000)
Background: Early evaluation of the severity of acute pancreatitis requires measurements of many variables. Clinical parameters as well as CT scan have traditionally been used as predictors of severity, and complications. None of them however can predict the outcome early and reliably. Inflammatory cytokines were shown to play an important role in the inflammatory cascade, which occurs early in the course of the disease. The aim of the present study is to evaluate the predictive value of plasma interleukin-6 (IL-6) and interleukin-1 (IL-1) levels in experimental pancreatitis in rats. Methods: Male wistar rats were anesthetized and pancreatitis was induced by intraparenchymal injection of 5% (group 2) and 10% (group 3) sodium taurocholate (TC), resulting in 2 distinct groups of severity. In sham controls (group 1), saline was injected into the pancreas in the same fashion. Blood samples were obtained before and 2, 4, 24, and 96 hours after the induction of pancreatitis and plasma amylase, lipase, LDH, IL-1 and IL-6 levels were measured. Mortality was recorded every 8 hours. Pancreatitis severity was also assessed by histopathology. Results: Four hours after pancreatitis induction, plasma amylase, lipase and LDH levels were markedly increased in the pancreatitis groups. In the sham control group, moderate increases were also observed. No consistent significant difference in amylase, lipase or LDH levels was observed between the groups. At 2 hours from pancreatitis induction, IL-6 levels increased mildly in-groups 1 and 2, and decreased to the baseline levels at 24 hours. In-group 3, the increase in IL-6 levels was significantly higher then in-groups 1 and 2 (p=0.029 and 0.036 respectively), and correlated well with pancreatitis severity as defined by pathology (p=0.01) and mortality rates (p=0.037). No difference in IL-1 levels was observed at 2,4 and 24 hours from induction. At 96 hours IL-1 levels were higher in group 3 then in groups 1 and 2 (p=0.037). Conclusion: IL-6 plasma levels correlated well with the severity of the disease as reflected by the mortality rates and pathological score. IL-6 levels may be a reliable predictor of severity and mortality in acute pancreatitis. This marker can be used as early as 2 hours and up to 24 hours from the beginning of the inflammatory process. IL-1 levels at 96 hours also correlated with pathology, but were not found to predict outcome at the early phases of the disease.